2015
DOI: 10.1093/humrep/dev154
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin stimulates human sperm capacitation through the cyclic AMP/protein kinase A pathway

Abstract: This study was supported by grants from FONDECYT (1130341, E.S.D. and 1120056, P.M.) and FONCYT (PIP 2011-0496, S.P.-M). The authors have no conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 90 publications
3
32
1
Order By: Relevance
“…We previously demonstrated that Fn modulates cAMP levels and PKA activity during human sperm capacitation (Martinez‐Leon et al, ). Here, we determined the effects of capacitation on cAMP levels and PKA activity during the early events of sperm capacitation.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…We previously demonstrated that Fn modulates cAMP levels and PKA activity during human sperm capacitation (Martinez‐Leon et al, ). Here, we determined the effects of capacitation on cAMP levels and PKA activity during the early events of sperm capacitation.…”
Section: Resultsmentioning
confidence: 98%
“…We previously demonstrated that Fn‐mediated effects are specific and triggered by Fn‐integrin α 5 β 1 binding (Martinez‐Leon et al, ). In this study, the results suggest that the CB1 and TRPV1 receptors were indirectly activated through Fn‐integrin α 5 β 1 binding during sperm capacitation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations